2006
DOI: 10.1063/1.2396925
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of particle-particle collisions in a viscous liquid

Abstract: When two solid spheres collide in a liquid, the dynamic collision process is slowed by viscous dissipation and the increased pressure in the interparticle gap as compared with dry collisions. This paper investigates liquid-immersed head-on and oblique collisions, which complements previously investigated particle-on-wall immersed collisions. By defining the normal from the line of centers at contact, the experimental findings support the decomposition of an oblique collision into its normal and tangential comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
114
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 8 publications
13
114
0
Order By: Relevance
“…Joseph & Hunt (2004) examined oblique collisions between a particle and a wall. Later work by Yang & Hunt (2006) measured the coefficient of restitution for particle-particle collisions in a liquid and found a similar dependence on particle Stokes number. However, for Stokes numbers less than approximately 20 the authors observed that the target particle moved prior to impact due to the increase in hydrodynamic pressure as the impacting particle approached within a half a particle diameter.…”
Section: Introductionmentioning
confidence: 94%
“…Joseph & Hunt (2004) examined oblique collisions between a particle and a wall. Later work by Yang & Hunt (2006) measured the coefficient of restitution for particle-particle collisions in a liquid and found a similar dependence on particle Stokes number. However, for Stokes numbers less than approximately 20 the authors observed that the target particle moved prior to impact due to the increase in hydrodynamic pressure as the impacting particle approached within a half a particle diameter.…”
Section: Introductionmentioning
confidence: 94%
“…Also, we indicate the modifications of these expressions to account for viscous dissipation in the way suggested by Yang and Hunt (2006), and already implemented to predict collisional sediment transport (Berzi & Fraccarollo 2013). In this case, the coefficients of restitution are assumed to depend on the Stokes number, so that…”
Section: Trajectory Equationsmentioning
confidence: 99%
“…1,2 Coupling between solid and liquid motions, however, modulates the influence of immersed collisions on the stress and energy balance of mixture flows. Studies of immersed particle-wall 3,4 and particle-particle collisions 5 have documented how particle rebound is damped by liquid viscosity. In particle-wall collisions, liquid vorticity has also been found to play a role.…”
mentioning
confidence: 99%
“…3,5 To clarify the interplay between vortex motions and immersed collisions, we conducted experiments with both isolated and colliding spheres, in the pendulum configurations illustrated in Fig. 1.…”
mentioning
confidence: 99%